ANALISIS FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Ciu, Veronica; Widyasari, Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to obtain empirical evidence about the effect of business risk, fixed asset ratio, and firm size on capital structure with profitability as a moderating variable of companies listed in Indonesian Stock Exchange in the period of 2018-2020. Using 61 companies out of 198 companies, and using a purposive sampling method. Data were collected from financial reports published on the IDX's official website, www.idx.co.id and www.idnfinancials.com. This study uses Microsoft Excel 2010 and Eviews version 12. The result of the research indicate that firm size and profitability have a positive significant effect on the capital structure, fixed asset ratio have a negative significant effect on the capital structure, business risk does not have a significant effect on the capital structure, while profitability is not able to moderate the influence of business risk, fixed asset ratio, and firm size on the capital structure.